Afterword: Troubling identities and identifications. (December 2014) - Luibhéid, Eithne
This article argues that the essays in the special issue on 'Queer Migration, Asylum and Displacement' collectively problematize how official identity categories trouble, and are troubled by, queer and asylum-seeking migrants. It discusses the future research and activist possibilities that these essays open up.